Evaluation Of Government Policy On School From Home And Its Impact On Parents Stress Level In Bekasi City - Widiyono; Diana Prihadini; Siti Nurbaity; Heksawan Rahmadi; Roby Irvawan (Ilomata International Journal of Social Science, 2020)
In accordance with government policies on some provinces, starting Monday (3/16/2020) up to this very moment, the policy of learning/school from home is still being implemented, starting from kindergarten, elementary, junior high, and high school levels even to universities. This step was taken by the government to anticipate the spread of a new type of coronavirus or Covid-19 within the educational institutions. The direct impact of changes in the learning system, so-called ‘internet-based learning’, has forced various parties to follow and being adaptive to this government policy. On the one hand, this gives students and parents in general, the opportunity to approach new learning systems, but on the other hand, there are still many lacks of devices and readiness of parents to catch up with the system changes that are suddenly applied without the stage of socialization and preparation. For educators, especially elementary school teachers to secondary schools and leaders of educational institutions, the policies provide many opportunities as well as a threat, because there are needs for certain preparation for teachers to engage the education process with a completely different pattern from conventional learning. Parents of the students, also facing challenges outside their daily routine and various tasks and responsibilities in the office, which almost sudden now have to prepare, even assisting their children in learning through the internet. This certainly has a psychological impact on parents' stress. Seeing the above facts, it is deemed necessary to design an education system with a learning pattern at home, which is an internet-based education system that is able to create an atmosphere and learning process that is fun, stimulating, and challenge students to develop themselves optimally in accordance with their talents and abilities, and parents as a companion of their children in the process of learning from home may avoid psychological stress.